2011
DOI: 10.1002/ajmg.a.34028
|View full text |Cite
|
Sign up to set email alerts
|

Submicroscopic deletion in 7q31 encompassing CADPS2 and TSPAN12 in a child with autism spectrum disorder and PHPV

Abstract: We performed array comparative genomic hybridization utilizing a whole genome oligonucleotide microarray in a patient with the autism spectrum disorders (ASDs) and persistent hyperplastic primary vitreous (PHPV). Submicroscopic deletions in 7q31 encompassing CADPS2 (Ca(2+) -dependent activator protein for secretion 2) and TSPAN12 (one of the members of the tetraspanin superfamily) were confirmed. The CADPS2 plays important roles in the release of neurotrophin-3 and brain-derived neurotrophic factor. Mutations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 30 publications
2
16
0
Order By: Relevance
“…Haploinsufficiency of CADPS2 and TSPAN12 genes in the 7q31.31 region has been shown to contribute to ASD and PHPV, respectively. The patient in our study with the 7q31.3-q33 deletion shared similar phenotypes with this previously reported case, 6 such as dysmorphic facial features and developmental delays. However, ASD-related features were not significant in our patient because he suffered from more complicated symptoms such as heart failure and did not survive long enough to fully dissect the scope of his symptoms.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Haploinsufficiency of CADPS2 and TSPAN12 genes in the 7q31.31 region has been shown to contribute to ASD and PHPV, respectively. The patient in our study with the 7q31.3-q33 deletion shared similar phenotypes with this previously reported case, 6 such as dysmorphic facial features and developmental delays. However, ASD-related features were not significant in our patient because he suffered from more complicated symptoms such as heart failure and did not survive long enough to fully dissect the scope of his symptoms.…”
Section: Discussionsupporting
confidence: 72%
“…Another report of a patient confirmed with a 5.4-Mb deletion in the 7q31.31 region had congenital nystagmus due to bilateral persistent hyperplastic primary vitreous (PHPV), which phenotypically overlaps with FEVR. 6 However, this patient was determined to not have FEVR. He had dysmorphic facial features such as low set ears and developmental delays, which led to an autism spectrum disorder (ASD) diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we demonstrated that neurons with increased expression of dex3 fail to properly coordinate local BDNF release from axons [14], [15]. In addition, the association of CAPS2 with autism has been suggested not only by the presence of copy number variations in the CAPS2 gene in autistic patients [17][19], but also by decreased transcription of CAPS2 in the brains of people with autism [20]. Recently, it was also reported that CAPS2 deletion and missense mutations of maternal origin contribute to onset [21].…”
Section: Introductionmentioning
confidence: 84%
“…Quite recently a submicroscopic deletion of 5.4 Mb size was detected in a three-year-old boy with autism spectrum disorder that encompassed just 20 genes [65]. These 20 genes included the autism-candidate genes, CADPS2 and TSPAN12 , but also the receptor tyrosine phosphatase, RPTP β/ζ ( PTPRZ1 ).…”
Section: Overview Of Mutations In Wnt Pathway In Patients With Asd (Pmentioning
confidence: 99%